Integrating robotic surgery training and the educational value of body donation: insights from an Italian pilot project on perceived training value - Irene Neri; Laura Forni; Simone Lodi; Clarissa A. E. Gelmi; Stefano Leto; Elisa Boschetti; Matteo Serenari; Lorenzo Bianchi; Paolo Bernante; Matteo Rottoli; Riccardo Schiavina; Matteo Cescon; et al. (Frontiers in Medicine, 2026)
Background Robotic-assisted surgery requires training that integrates technical skills, visuospatial coordination, platform management, and anatomical understanding. Although synthetic and virtual-reality simulators are widely used, high-fidelity training on bodies donated to science remains comparatively underreported. This pilot study therefore aimed to evaluate participants’ perceived value of a robotic surgery training experience with the da Vinci Xi platform in a body donation setting, and to examine whether this perceived value was associated with participants’ views on the educational role of body donation. Methods This pilot post-course mixed-methods evaluation involved 41 residents and surgeons in general surgery and urology. The program combined dry-lab and wet-lab activities using the da Vinci Xi platform and three body donors. Participants completed a study-specific questionnaire including seven Likert-type items and two open-ended questions. Quantitative data were analyzed descriptively, through Spearman correlations and exploratory subgroup comparisons; qualitative responses underwent thematic analysis. Results Course evaluations ratings were highly positive, with mean scores ranging from 4.59 to 4.88 on a 5-point scale. The mean Training Value Index was 4.70, and the five course evaluation items showed good internal consistency. All participants expressed high willingness to attend a similar course again, and 97.6% would recommend it to colleagues. Agreement that body donation represents a gold standard for medical and surgical education and training, and its perceived ethical importance, received high ratings from 95.1 and 97.6% of participants, respectively. Both were significantly associated with the Training Value Index. Qualitative feedback highlighted hands-on robotic practice, anatomical fidelity, operative-like workflow, and requests for longer or repeated training opportunities. Conclusion Participants perceived robotic surgery training in a body donation setting as highly valuable, and this perception was closely linked to their broader recognition of the educational value of body donation. These preliminary findings suggest that combining technical training, anatomical complexity, team-based workflow, and ethical awareness may represent a promising complement to dry-lab and virtual-reality simulation, warranting further investigation to inform the development of more integrated robotic surgery curricula.